2003
DOI: 10.1002/cncr.11233
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with treatment decisions for clinically localized prostate carcinoma. Results from the Prostate Cancer Outcomes Study

Abstract: BACKGROUNDMen with early‐stage prostate carcinoma can choose aggressive treatment or conservative management. The authors used data from a population‐based cohort of men with clinically localized prostate carcinoma to describe satisfaction with treatment decisions 24 months after diagnosis and to examine the association of demographic, socioeconomic, and clinical characteristics with treatment satisfaction.METHODSThe authors evaluated 2365 men with clinically localized prostate carcinoma, diagnosed between Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
115
0
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 26 publications
10
115
0
11
Order By: Relevance
“…18 In line with our results, Hoffman and colleagues showed that 75% of those who developed daily urinary incontinence still reported that the poor function was at most only a small problem. 19 Consequently, the recovery from urinary bother was observed early at 6 months and in the remaining postoperative periods, showing that postoperative incontinence was, if any, minimal in the majority of the patients and their problems were not so severe.…”
Section: Discussionmentioning
confidence: 88%
“…18 In line with our results, Hoffman and colleagues showed that 75% of those who developed daily urinary incontinence still reported that the poor function was at most only a small problem. 19 Consequently, the recovery from urinary bother was observed early at 6 months and in the remaining postoperative periods, showing that postoperative incontinence was, if any, minimal in the majority of the patients and their problems were not so severe.…”
Section: Discussionmentioning
confidence: 88%
“…There did not seem to be any statistical differences in terms of ED in between the types of ADT therapy. In a later study 64 by the same group, 86% of men undergoing ADT subsequently experienced ED, compared to 58% of radical prostatectomy patients, 43% of radiotherapy patients and 33% patients undergoing watchful waiting (P,0.0001). In another study by Potosky et al, 65 the erectile function outcomes of a cohort of 88 ADT patients were compared to a matched group of 223 prostate cancer patients receiving no treatment.…”
Section: Edmentioning
confidence: 88%
“…Örneğin, Hoffman ve ark.nın yaptıkları çalışmada, İspan-yol kökenli hastaların diğer hastalara göre memnuniyetlerinin daha düşük olduğu belirtilmekte ve hastalığın algılanması ile tedavi memnuniyetinin etnik kökene bağlı olarak değişkenlik gösterebil-diği vurgulanmaktadır. 12 Bu çalışmanın sonuçları ülkemizdeki etnik ve/veya sosyokültürel farklılık-lara göre tedavi algısını değerlendirmek için yeterli düzeyde olmamakla beraber, genel sonuçların dünya literatürü ile uyumlu olması ileride daha yüksek hasta sayısı ile yapılacak olan çalışmalarda bu faktörün ülkemiz için ne derecede önemli olduğunu ortaya çıkarabilecektir.…”
Section: Discussionunclassified
“…G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Lokalize prostat kanseri nedeniyle 2003 ve RT alan 39 (%46,5) olgunun tedavi kararı ve memnuniyetleri ile tedavi sonrası ilişkili parametreleri 17 sorudan oluşan bir form ile değerlendirilmiş ve her iki hasta grubunun verileri birbiriyle karşılaştırılmıştır. B Bu ul lg gu ul la ar r: : RT ve RRP uygulanan hastaların ortalama yaşı sırası ile 72,12 ±5,41 ve 62,63 ±8,46 yıldır (p<0,001).…”
unclassified